Rational chemical applications of explosion-graphene - Covarrubias, Jose Jesus (Kansas State University, 2021)
Cancer is a very complex disease that has zero respect for humans; it affects every human being no matter what age, gender, race, or ethnicity they come from. It is among the leading causes of deaths worldwide. In the United States alone, it is the second leading cause of death. On average, there are approximately 4 new cancer cases and 1 death every minute. For this reason, researchers have explored the use of several materials in the development of novel strategies to fight cancer. Fortunately, thanks to the extraction of graphene (a honeycomb sheet of carbon atoms) and the discovery of its extraordinary properties in 2004, graphene became the wonder material of the 21st century due to its unique properties, including excellent electrical and thermal conductivity, optical transparency, and mechanical strength. For this reason, many researchers were inspired to explore the possibility of using graphene in cancer applications; however, it has been difficult to take complete advantage of graphene’s exceptional properties because large-scale production methods are neither simple nor economical. For this reason, the goal of this dissertation was to overcome one of the greatest challenges in mass-producing high-quality graphene materials in a reproducible way at low cost that could be easily modified and used in a variety of areas such as nanoelectronics, sensors, batteries, supercapacitors, and in biomedicine including cancer applications. Therefore, we have synthesized the first known turbostratic core/shell graphene oxide which is designed to incorporate the unique physical and materials properties of graphene into numerous materials. This was accomplished by oxidizing high-quality explosion synthesized few-layer graphene by means of Fenton oxidation. Additionally, the reaction was successfully scaled up from 1.0 g batch to 200g per batch maintaining all of graphene’s extraordinary properties intact because only the surface layers of few-layer graphene get oxidized during Fenton oxidation. Furthermore, we have developed a graphene-based nanobiosensor for the early detection of lung cancer, which causes the highest number of deaths than any other type of cancer in the United States. Based on the results, our graphene-based nanobiosensor was able to detect biomarkers down to the sub-femtomolar level after 1 hour of incubation. This presents a promising opportunity to detect lung cancer at a much earlier stage. This is very important in lung cancer detection because cancer survival significantly increases when it is detected at stages 0, 1 compared to 3 or 4.
Keywords: Explosion-synthesized graphene; Fenton oxidation; Graphene/graphene oxide core/shell particles; Graphene-based nanobiosensor